The Use of Inquiry-Based Mobile Pocket Book on Students’ Knowledge Based on Critical Thinking Skills on Global Warming - Sarwanto, Sarwanto; Febrianti, Valinda Putri; Zahroh, Shofi Hikmatuz (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
The purpose of this study was to analyze: (1) differences in the effect of using learning media mobile pocket book and electronic book on student knowledge learning outcomes on Global Warming material, (2) differences in the effect of critical thinking skills with high and low categories on student knowledge learning outcomes on Global Warming material, (3) interaction between learning media mobile pocket book and electronic book with critical thinking skills on student knowledge learning outcomes on Global Warming material. This study used a quasi-experimental method with a sample of grade XI students’ divided into two classes. The data analysis technique used was Kruskal-Wallis Test. The results showed: (1) there is a difference in the effect of using learning media mobile pocket book and electronic book on student knowledge learning outcomes, (2) there is no difference in the effect of critical thinking skills with high and low categories on student knowledge learning outcomes on Global Warming material, (3) there is an interaction between learning media mobile pocket book and electronic book with critical thinking skills on student knowledge learning outcomes on Global Warming material.